Key use cases for artificial intelligence to reduce the frequency of adverse drug events: a scoping review - Syrowatka, Ania; Song, Wenyu; Amato, Mary G; Foer, Dinah; Edrees, Heba; Co, Zoe; Kuznetsova, Masha; Dulgarian, Sevan; Seger, Diane L; Simona, Aurélien; Bain, Paul A; Purcell Jackson, Gretchen; et al. (The Lancet. Digital health, 2022)
Adverse drug events (ADEs) represent one of the most prevalent types of health-care-related harm, and there is substantial room for improvement in the way that they are currently predicted and detected. We conducted a scoping review to identify key use cases in which artificial intelligence (AI) could be leveraged to reduce the frequency of ADEs. We focused on modern machine learning techniques and natural language processing. 78 articles were included in the scoping review. Studies were heterogeneous and applied various AI techniques covering a wide range of medications and ADEs. We identified several key use cases in which AI could contribute to reducing the frequency and consequences of ADEs, through prediction to prevent ADEs and early detection to mitigate the effects. Most studies (73 [94%] of 78) assessed technical algorithm performance, and few studies evaluated the use of AI in clinical settings. Most articles (58 [74%] of 78) were published within the past 5 years, highlighting an emerging area of study. Availability of new types of data, such as genetic information, and access to unstructured clinical notes might further advance the field.